IMPROVING PERFORMANCE AND THERMOTOLERANCE STATE OF THERMALLY STRESSED BROILER’S USING SUPPLEMENTED NATURAL ANTIOXIDANTS - Sh. Dh. Mohammad; S. Y. Al-Sardary (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The aim of this experiment was studying the efficacy dietary dried powders’ of ecofriendly natural antioxidants of beetroot (Br), grape pomace (Gp) and willow (W) in two concentrations 0.5 and 1 % as an anti-heat-stressor and their impacts on performance and thermo-tolerance state on broiler’s housed under thermal-stress averaged (33◦C). 630 Ross-308day-old-chicks were used. The treatments were applied after 2 weeks of starter feeding as beginning grower feed then finisher diet until 42d marketing age. The treatments were as follow: T1:Control (basal diet BD); T2 (1% Br+BD); T3 (0.5% Br+BD); T4 (1%GP+BD); T5 (0.5%GP+BD); T6 (1%W+BD); T7 (0.5%W+BD). Complete Random Design (CRD) used on three replicates/treatment; thirty bird/rep. The results indicate that both Br and Gp in both (0.5; 1%) levels improved growth performance except birds in W 0.5% wasn’t affected and W 1% decreased significantly than Control. The PEF was significantly higher in each of T2, T3, and T4 groups than Control group. All natural antioxidants dietary supplemented enhanced body antioxidants; prevented oxidation; developed thermo-tolerance and stress expressions than the control group. It can be concluded that the antioxidant property of the eco-friendly additives used in the current experiment promoted the biological condition hence the thermally-stressed broilers’ productive performance.